PRONOMINAL USAGE IN JAMBI MALAY - ., Hustarna (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This paper discusses the pronominal usage in Jambi Malay. The pronouns are described in term of their socio-semantics. The use of pronouns in Jambi Malay correlates to the interlocutors’ social attitudes and the ages of the speaker and the addressee. Thus, age plays an important role in deciding between pronoun forms. Pronouns in Jambi Malay neither show gender nor social status.Keywords: pronominal usage,Jambi Malay